Influence of injection technique, drug formulation and tumor microenvironment on intratumoral immunotherapy delivery and efficacy. Issue 2 (15th February 2021) - Muñoz, Nina M.; Williams, Malea; Dixon, Katherine; Dupuis, Crystal; McWatters, Amanda; Avritscher, Rony; Manrique, Soraya Zorro; McHugh, Kevin; Murthy, Ravi; Tam, Alda; Naing, Aung; Patel, Sapna P.; et al.
Abstract : Background: Intratumoral delivery of immunotherapeutics represents a compelling solution to directly address local barriers to tumor immunity. However, we have previously shown that off-target delivery is a substantial problem during intratumoral injections; this can lead to diminished drug efficacy and systemic toxicities. We have identified three variables that influence intratumoral drug delivery: injection technique, drug formulation and tumor microenvironment. The purpose of this study was to characterize the impact of modifications in each variable on intratumoral drug delivery and immunotherapy efficacy. Methods: Intratumoral injections were performed in a hybrid image-guided intervention suite with ultrasound, fluoroscopy and CT scanning capabilities in both rat and mouse syngeneic tumor models. Intratumoral drug distribution was quantified by CT volumetric imaging. The influence of varying needle design and hydrogel-based drug delivery on the immune response to a stimulator of interferon genes (STING) agonist was evaluated using flow cytometry and single cell RNA sequencing. We also evaluated the influence of tumor stiffness on drug injection distribution. Results: Variations in needle design, specifically with the use of a multiside hole needle, led to approximately threefold improvements in intratumoral drug deposition relative to conventional end-hole needles. Likewise, delivery of a STING agonist through a multiside hole needle led to significantly increased expression of type I interferon-associated genes and 'inflammatory' dendritic cell gene signatures relative to end-hole STING agonist delivery. A multidomain peptide-based hydrogel embedded with a STING agonist led to substantial improvements in intratumoral deposition; however, the hydrogel was noted to generate a strong immune response against itself within the target tumor. Evaluation of tumor stroma on intratumoral drug delivery revealed that there was a greater than twofold improvement in intratumoral distribution in soft tumors (B16 melanoma) compared with firm tumors (MC38 colorectal). Conclusions: Injection technique, drug formulation and tumor stiffness play key roles in the accurate delivery of intratumoral immunotherapeutics.